FRI0153 Comparison of cardiovascular risk in patients with rheumatoid arthritis treated with biologics versus methotrexate: results at 24-months of follow-up. (15th June 2017) - Khraishi, M; Stutz, M; Lewis, A; Molta, C; Rampakakis, E
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased risk of atherosclerotic cardiovascular (CV) disease. Treatment with conventional systemic disease modifying drugs (csDMARDs) such as methotrexate (MTX), as well as biological DMARDs (bDMARDs), has been shown to decrease CV risk. Although bDMARDs specifically target inflammation common to RA and atherosclerosis, whether or not cardioprotective effects associated with bDMARD use is superior to csDMARDs, remains to be determined. Objectives: To investigate 10 year-CV risk, and incidence of new myocardial infarctions (MI), in RA patients treated with either MTX or bDMARD mono/combination therapy, in a Canadian routine clinical care setting Methods: RA patients were prospectively followed between January 2011-March 2014. Parameters collected were patient demographics, RA disease activity parameters, traditional CV risk factors, lipid parameters, and 10-year CV risk, assessed using the Framingham Risk Score (FRS). Between-group differences in change from baseline to month 24 in FRS, disease activity, and lipid parameters were assessed with the two sample t-test or the Chi-Square statistic; within-group differences were assessed with the paired-samples t-test or the McNemar-Bowker test. Adjusted change in FRS was ascertained using general linear models, and logistic regression identified predictors of MI. Results: A total of 517 RA patients receiving bDMARDs (n=313) or MTX (n=199), were included. Mean (SD) age was comparable between cohorts [57.57 (12.11) years vs. 59.58 (12.60), p=0.11; bDMARD vs. MTX, respectively], as was female gender (76.7% vs. 73.9%, p=0.268). Patients receiving bDMARDs had significantly (p<0.05) longer mean (SD) RA duration [12.63 (9.95) vs. 7.88 (6.94) years] and higher total comorbidities [3.96 (2.53) vs. 3.38 (2.32)]. Mean (SD) baseline FRS was 11.84 (9.38) vs. 12.36 (9.19) percent (p=0.564; bDMARDs vs. MTX, respectively), and patient distribution across low (62.3% vs. 54.8%), intermediate (9.9% vs. 12.2%) and high (27.8% vs. 33.2%) FRS risk categories was comparable (p=0.239). At month 24, FRS category remained stable in bDMARD patients (low: 58.8%; intermediate: 14.2%; high: 27.0%; p=0.380), whereas a shift in FRS category was observed in MTX patients (low: 69.6%; intermediate: 10.1%; high: 27.0%, p=0.006). Within-group changes in FRS were significant for both MTX (p<0.001) and bDMARD patients (p=0.016). Adjusted mean change (SE) in FRS was higher in MTX patients [-1.37 (0.30) vs. -0.72 (0.25)], although not statistically different (p=0.098). Incidence of new MI was similar between groups (MTX: 3.8% vs. dDMARD: 3.0%; p=0.421), and predictors [OR (95% CI)] identified were: higher total comorbidities [1.45 (1.24, 2.20), p<0.001], age [1.07 (1.00, 1.13), p=0.037], and male gender [4.00 (1.38, 11.57), p=0.011]. Conclusions: Significant improvement in CV risk at 24 months was observed during treatment with both MTX and bDMARDs. As predictors of MI did not include several established CV risk factors, longer studies, as well as the development of an RA-specific tool, may permit better assessment of CV risk in RA patients. Disclosure of Interest: M. Khraishi Grant/research support from: Roche Canada, M. Stutz: None declared, A. Lewis: None declared, C. Molta: None declared, E. Rampakakis: None declared